Molecular cloning of DNA (Shrewsbury, MA : Science Fision International)
This volume set of video is designed to provide you the complete understanding of each and every aspect of DNA Cloning Techniques - vol.1: introduction, restriction & modifying enzymes, genomic library, plasmid preparation, gel electrophoresis, DNA subcloning, DNA hybridization - vol.2 : southern blot & its applications, dot blot, DNA sequencing, DNA mulations, PCR (polymerase chain reaction), DNA footprinting, nuclease S 1 protection assy, polyacrylamide gel electrophoresis, western blot
Keywords: Cloning, Molecular; DNA